Performa Kesehatan Ikan Nila Salin (Oreochromis niloticus) Terhadap Pakan Sinbiotik Bacillus subtilis yang Diuji Tantang dengan Aeromonas hydrophila - R Rahmi; Andi Ninnong Renita Relatami; A Akmal; Bunga Rante Tampangallo; Iman Sudrajat; Nur Insana Salam; Andi Chadijah; Fitri Indah Yani (JURNAL GALUNG TROPIKA, 2022)
This study aims to determine the health of saline tilapia (Oreochromis niloticus) on feeding containing synbiotics, namely probiotic bacteria Bacillus subtilis and 1% banana flour prebiotic against pathogenic infections by looking at parameters such as blood picture and phagocytic activity. This study consisted of 4 treatments and three replications, namely artificial feed treatment without the addition of B. subtilis, artificial feed with the addition of B. subtilis 105CFU/mL, artificial feed with the addition of B. subtilis 107CFU/mL, and artificial feed with the addition of B. subtilis 109CFU/mL with the number of samples used as many as 20 tails/treatment. Parameters for observing blood picture (erythrocytes, leukocytes and hematocrit) and phagocytic activity. The number of erythrocytes treated with artificial feed with the addition of B. subtilis 107CFU/mL was 5.50x106cell/mm3, and the lowest was obtained in the treatment with the addition of B. subtilis 105CFU/mL, which was 3.5x106cell/mm3. The highest leukocytes were obtained in the treatment with the addition of bacteria B. subtilis 105CFU/mL, which was 2.71x104cell/mm3. The hematocrit value of saline tilapia was in the same range of 25.83%-56.56%. The results showed that the treatment with the addition of 1% banana flour prebiotic and a dose of 105CFU/mL of probiotic B. subtilis in the feed was able to increase the immune system response of the saline tilapia.